Young Children in Humanitarian and COVID-19 Crises Innovations and Lessons from the Global South - Shah, Sweta; Bassett, Lucy (Routledge Humanitarian Studies, 2024)
The long-term consequences of COVID-19 have been tough for children around the world, but even more so for young children already in humanitarian crisis, whether due to conflict, natural disasters, or economic and political upheaval. This book investigates how organizations around the world responded to these dual challenges, identifying solutions, and learning opportunities to help to support young children in ongoing and future crises. Drawing on research and voices from the Global South, this book showcases innovations to mobilize new funds and re-allocate existing resources to protect children during the pandemic. It provides important evidence on understudied and overlooked vulnerable populations, recognizing that researchers from the Global South are best positioned to fill these research gaps, contextualize findings, and support the uptake and adoption of recommendations by local decision-makers and practitioners in those same contexts. The findings in this book will be important for practitioners, policy makers and donors working in or interested in humanitarian contexts, on early childhood development, or early childhood education. The book will also be useful to students and researchers working in these fields. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.